Optimization of simultaneously enzymatic fructo- and inulo-oligosaccharide production using co-substrates of sucrose and inulin from Jerusalem artichoke. Issue 2 (7th February 2018) - Kawee-ai, Arthitaya; Ritthibut, Nuntinee; Manassa, Apisit; Moukamnerd, Churairat; Laokuldilok, Thunnop; Surawang, Suthat; Wangtueai, Sutee; Phimolsiripol, Yuthana; Regenstein, Joe M.; Seesuriyachan, Phisit
ABSTRACT: Prebiotic substances are extracted from various plant materials or enzymatic hydrolysis of different substrates. The production of fructo-oligosaccharide (FOS) and inulo-oligosaccharide (IOS) was performed by applying two substrates, sucrose and inulin; oligosaccharide yields were maximized using central composite design to evaluate the parameters influencing oligosaccharide production. Inulin from Jerusalem artichoke (5–15% w/v), sucrose (50–70% w/v), and inulinase from Aspergillus niger (2–7 U/g) were used as variable parameters for optimization. Based on our results, the application of sucrose and inulin as co-substrates for oligosaccharide production through inulinase hydrolysis and synthesis is viable in comparative to a method using a single substrate. Maximum yields (674.82 mg/g substrate) were obtained with 5.95% of inulin, 59.87% of sucrose, and 5.68 U/g of inulinase, with an incubation period of 9 hr. The use of sucrose and inulin as co-substrates in the reaction simultaneously produced FOS and IOS from sucrose and inulin. Total conversion yield was approximately 67%. Our results support the high value-added production of oligosaccharides using Jerusalem artichoke, which is generally used as a substrate in prebiotics and/or bioethanol production.